МЕКТЕПКЕ ШЕКЕМГИ ЖАСТАҒЫ БАЛАЛАРДА ОПЕРАЦИЯЛЫҚ ОЙЛАЎДЫ ҚӘЛИПЛЕСТИРИЎДИҢ ПСИХОЛОГИЯЛЫҚ АЙРЫҚШАЛЫҚЛАРЫ - Уразимова, Т.В. (FAN va JAMIYAT, 2024)
The article is devoted to the problem of psychological characteristics of the formation of operational thinking in pre-school children. The age-related characteristics of children's operational intelligence are considered.